(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The results of algae investigation from the seacost solonchaks in Pryazovskyi region are presented. 140 species and intraspecial taxa were found from the phylum: Cyanophyta - 69 species (76 intraspecial taxa), Chlorophyta – 44 species (45 intraspecial taxa), Bacillariophyta – 16 species, Xanthophyta – 3 species. The dominating families, genera and specific species for solonchak soil (18 species) were identified. Distribution and ecotopical analyses of the algae that were found on the territory of Ukraine are given. 4 new species for the flora of Ukraine were described: Chroococcus pulcherrimus, Pseudanabaena limnetica, Oscillatoria salina, Pseudendoclonium sp. 7 algal communities and 4 synusias that forms macroscopical growth on the solonchak’s soil surface are defined.